PENGARUH KOMUNIKASI ORGANISASI, BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KOMITMEN ORGANISASI PADA ORGANISASI MAHASISWA UNIVERSITAS PELITA BANGSA - Ahmad Badawi; Duriyyatul Millah; Lutfiyah Apriliani; Intan Nur Cahyani; Syahratu Intan Azzahra; Alma Syifa Rahma Azizi; Zulaeka, Almira (CV. Denasya Smart Publisher, 2025)
This study aims to explore how organizational communication, organizational culture, and leadership style influence organizational commitment within student organizations at Universitas Pelita Bangsa. A total of 75 active student organization members participated as respondents, selected using a purposive sampling technique. Data were analyzed using the Partial Least Squares (PLS) approach with SmartPLS 3.0 software. The findings reveal that both organizational communication and culture significantly impact the level of commitment among student organization members. However, leadership style was found to have no significant effect on organizational commitment. These results highlight the crucial role of communication and culture in fostering strong organizational commitment, which contributes to the overall success of student organizations